Clearance Analysis and Leakage Flow CFD Model of a Two-Lobe Multi-Recompression Heater - Ashish M. Joshi; David I. Blekhman; James D. Felske; John A. Lordi; Joseph C. Mollendorf (International Journal of Rotating Machinery)
This paper reports the results of a study on multi-recompression heating. This process employs a Roots-type mechanism to heat gases to very high temperatures by compressive gas heating. A CFD model predicting the leakage flows in the machine was developed, and an excellent comparison with experimental data taken on a two-lobe Roots blower was obtained. A “clearance analysis” was performed to show that the clearance between the impellers remains constant for 96% of the angles of rotation. Assuming a quasi-steady state, the CFD simulation was performed for a single angle of rotation. A three-dimensional analysis showed that the flow field is identical along the rotor length, except for the leakage through the end plates. Hence, the model was further simplified to a two-dimensional analysis. This research may provide guidance in predicting the leakage flows in other blowers of the same kind with a different geometry.